Preparation method and application of coal-based carbon tube composite graded porous carbon material
By using cable extraction method and pyrolysis treatment technology in supercapacitor carbon materials, the carbon nanotube/activated carbon composite materials are generated, which solves the problem of single pore structure and low specific surface area utilization of existing materials, which significantly improves the Specific capacitance and rate performance.
Patent Information
- Application Number
- CN202411659596.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-18
AI Technical Summary
The existing supercapacitor carbon materials have a single pore structure and low specific surface area utilization, resulting in poor specific capacitance and rate performance.
The light components in low-order coal were removed by cable extraction, combined with alkali metal catalyst and sulfate additives for pyrolysis to produce carbon nanotubes/activated carbon composite materials, and the materials were optimized by acid-eluting ash treatment. structure.
The specific surface area and multi-stage pore structure of the material are significantly improved, and the specific capacity and rate performance are optimized. The specific surface area of the material is about 1300~1800 m2/g, the mesoporosis is 12%~28%, and the specific capacity can reach 240~310. F/g.
Smart Images

Figure CN119461344A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the cross-technical field of coal science and carbon materials, and in particular to a preparation method and application of a coal-based carbon tube composite graded porous carbon material. Background Art
[0002] Supercapacitors are a new type of energy storage device that has attracted much attention. They have excellent charge and discharge rates, long cycle stability, high energy density and power density. In recent years, they have been widely used in electric vehicles, smart grids and mobile power supplies. According to different energy storage principles, supercapacitors are divided into double-layer capacitors, pseudocapacitors and hybrid capacitors. Double-layer capacitors generate reversible electrostatic adsorption on the contact surface between the electrode and the electrolyte to form a double layer to store charge; pseudocapacitors store and release charge through reversible redox reactions on the electrodes. Among them, the electrode material is the key factor affecting the performance of supercapacitors. Among various electrode materials, functional carbon materials such as activated carbon and carbon nanotubes have become the main electrode materials because of their advantages such as large specific surface area, good pore structure, conductivity and chemical stability.
[0003] Studies have found that the specific surface area and pore structure of activated carbon significantly affect the performance of double-layer capacitors. CN111232975 A discloses "activated carbon materials for supercapacitors and their preparation methods and applications". The specific surface area of activated carbon materials derived from grapefruit seeds is 38.999~1187.439 m 2 / g, pore volume is 0.398~0.616 cm 3 / g, due to the small specific surface area, there is a lack of sufficient active sites to accumulate charge, so the specific capacitance of the material is poor. CN 108101054 A discloses a "method for preparing supercapacitor activated carbon with controllable specific surface area", which is obtained through crushing, drying, dry distillation, multiple pore making and other steps to obtain coconut shell-based capacitor carbon with a specific surface area of 2000~2200 m 2 / g, but the specific capacitance is only 60~80 F / g, which shows that there is no simple linear relationship between specific surface area and specific capacitance. The small pore size hinders the migration and diffusion rate of electrolyte ions. Therefore, when developing high-performance capacitive carbon materials, it is necessary to reasonably design the pore structure while increasing the specific surface area and increase the mesoporous ratio. In addition, the environmental pressure and energy consumption problems brought about by the cumbersome carbonization-activation process should also be taken into account. Summary of the invention
[0004] Aiming at the problem that the existing supercapacitor carbon has a single pore structure and low specific surface area utilization, resulting in poor specific capacitance performance and rate performance, the present invention provides a method for preparing a coal-based carbon tube composite hierarchical porous carbon material.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a coal-based carbon tube composite hierarchical porous carbon material, comprising the following steps: (1) Using the Soxhlet extraction method to remove light components from low-rank coal to obtain residual coal; (2) The raffinate coal obtained in step (1) is mixed evenly with an alkali metal catalyst and a sulfate additive, water is added and stirred, and the mixture is dried in an oven overnight, and then fully ground; (3) placing the mixture obtained in step (2) into a sealed metal reactor and heating it in a muffle furnace, and after the product is cooled, a crude product containing carbon nanotubes / activated carbon is obtained; (4) The crude product obtained in step (3) is subjected to acid washing and deashing treatment with nitric acid or hydrochloric acid at 60-80° C. to reduce the ash content to below 0.5%, and then filtered, washed with water to neutrality, and dried to obtain a coal-based carbon tube composite hierarchical porous carbon material.
[0006] The principle of the present invention is as follows: The present invention uses low-rank coal or sub-bituminous coal as raw materials, and uses organic solvents to perform specific extraction on coal (similar dissolves in the same), which can pre-remove some light components in the raw coal skeleton, pre-generate a part of the pores in the subsequent activation process, and then generate new micropores and expand the generated pores under the action of the activator, so as to obtain a developed specific surface area and hierarchical porous structure. This structure helps to adsorb a large amount of charge and provide a fast transmission channel for electrolyte ions, thereby optimizing the specific capacity and rate performance of the supercapacitor. The carbon nanotubes in the product come from the catalytic growth of alkali metal-S in a closed container: during the high-temperature pyrolysis process, carbon-containing gas (methane) and aromatic hydrocarbons and other active carbon species are released from the coal, and multi-walled carbon nanotubes are grown from carbon atoms and carbon clusters under the catalytic action of alkali metal-S. The developed pore structure is not conducive to the graphitization structure and conductive properties of the material, but the conductivity of carbon nanotubes is better than that of activated carbon, which can effectively reduce the internal resistance of the material, achieve a balance between the pore structure and conductivity at a low cost, and obtain the best electrochemical performance.
[0007] As a further limitation of the technical solution of the present invention, the specific steps of the Soxhlet extraction method in step (1) are: loading the dry low-rank coal powder into a Soxhlet extraction cylinder, and injecting a low-boiling point organic solvent into the container below; after connecting the various parts of the extractor, connecting condensing water, and setting the temperature of the organic solvent constant temperature water bath to 80-140°C; extracting until the liquid in the extraction cylinder is transparent and colorless, placing the remaining coal sample in the extraction cylinder in an oven at 80°C and drying for 3 hours to obtain the residual coal, and recycling the organic solvent waste liquid by evaporation-condensation.
[0008] As a further limitation of the technical solution of the present invention, in step (1), the low-rank coal is one or more of lignite, long flame coal and sub-bituminous coal, and low-ash coal is preferred; the low-boiling point organic solvent is one or more of tetrahydrofuran, toluene and carbon disulfide; and the ratio of coal to organic solvent is 1 g:10~50 mL.
[0009] As a further limitation of the technical solution of the present invention, the extraction rate (the percentage of the mass loss of the extracted coal to the mass of the raw coal) in step (1) is greater than 20%.
[0010] As a further limitation of the technical solution of the present invention, in step (2), the mass ratio of the extracted coal to the alkali metal catalyst and the sulfate additive is 1:1~3:0~0.05.
[0011] As a further limitation of the technical solution of the present invention, the alkali metal catalyst described in step (2) is at least one of KOH, K2CO3, C6H5K3O7, NaOH and Na2CO3, and the sulfate is one of K2SO4 and Na2SO4.
[0012] As a further limitation of the technical solution of the present invention, the stirring time in step (2) is 6 to 12 h, and the drying temperature of the mixture in the oven is 110°C.
[0013] As a further limitation of the technical solution of the present invention, the material of the metal reactor in step (3) is one of high temperature and corrosion resistant 316S and 316L stainless steels, and the wall thickness is less than 5 mm; the heating conditions in the muffle furnace are: heating to 750-950°C at a heating rate of 5-15°C / min and maintaining the temperature for 1-3 h.
[0014] As a further limitation of the technical solution of the present invention, the concentration of nitric acid or hydrochloric acid in step (4) is 1-2 mol / L, and the deashing treatment time is 6-12 h.
[0015] The present invention also provides the use of the coal-based carbon tube composite hierarchical porous carbon material obtained by the above-mentioned preparation method in the preparation of supercapacitors.
[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention prepares supercapacitor carbon based on a specific extraction plus one-step activation method. The process is simple, avoids the environmental pressure brought by the traditional carbonization-activation process, significantly reduces energy consumption, greatly saves costs, and the by-products obtained by extraction can also be used to prepare high-quality oil.
[0017] 2. The present invention optimizes the specific surface area and multi-level pore structure of activated carbon, and the material exhibits excellent specific capacity and rate performance: the specific surface area is about 1300~1800 m 2 / g, the mesoporosity is 12%~28%, and its specific capacity can reach 240~310 F / g at a current density of 1 A / g.
[0018] 3. The raw materials of the present invention are widely available, the equipment is simple, the production cycle is short, and it is expected to achieve mass production.
[0019] 4. The present invention prepares carbon nanotubes at a very low cost, which can form a soft and dense three-dimensional conductive network with activated carbon particles, improve the conductivity of the material and reduce the internal resistance of the electrode; in addition, it can replace conductive additives such as graphite and carbon black, further simplifying the preparation process of supercapacitors and reducing costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a process flow chart of the present invention.
[0021] Figure 2 This is a scanning electron microscope image of the coal-based carbon tube composite hierarchical porous carbon material obtained in Example 1.
[0022] Figure 3 1. The nitrogen adsorption-desorption curve and pore size distribution diagram of the coal-based carbon tube composite hierarchical porous carbon material obtained in Example 1.
[0023] Figure 4 The cyclic voltammograms of the electrode assembled in Example 1 at different scanning speeds.
[0024] Figure 5 The constant current charge and discharge diagrams of the electrodes assembled in Example 1 at different current densities. DETAILED DESCRIPTION
[0025] The present invention is further described below in conjunction with specific embodiments. Example 1
[0026] A method for preparing a coal-based carbon tube composite hierarchical porous carbon material, comprising the following steps: The lignite was subjected to Soxhlet extraction with tetrahydrofuran and toluene as solvents. The ratio of coal to organic solvent was 1 g:50 mL, and the extraction rate was 30%. The remaining coal sample in the extraction tube was placed in an oven at 80 °C for 3 h to obtain the residual coal. The residual coal was mixed with K2CO3 and K2SO4 in a mass ratio of 1:3:0.02, and after adding appropriate amount of water and stirring for 12 h, it was dried in an oven at 110 °C overnight and then fully ground. The mixture was loaded into a closed metal reactor and placed in a muffle furnace. It was heated to 850 °C at a heating rate of 5 °C / min and kept at a constant temperature for 2 h. After the product was cooled, a crude product containing carbon nanotubes / activated carbon was obtained. The crude product was deashed with 2 mol / L nitric acid and hydrochloric acid at 80 °C for 12 h to reduce the ash content to less than 0.5%, and then filtered, washed with water to neutrality, and dried to obtain a coal-based carbon tube composite hierarchical porous carbon material. Low temperature nitrogen adsorption-desorption analysis showed that the specific surface area of the material was 1775 m 2 / g, and the total pore volume is 0.81 cm 3 / g, and the mesoporosity is 12.4%.
[0027] The material was mixed with polyvinylidene fluoride (PVDF) at a mass ratio of 90:10, and a proper amount of N-methyl-2-pyrrolidone (NMP) was added to make a slurry and applied to a nickel foam with a diameter of 16 mm. After the solvent evaporated, it was placed in a vacuum drying oven at 100°C for 12 hours, and then a three-electrode test was performed with the nickel foam coated with active materials as the working electrode, metal platinum as the counter electrode, Hg / HgO as the reference electrode, and 6M KOH solution as the electrolyte. The electrochemical performance test showed that the material had excellent electrochemical performance for supercapacitors, and its cyclic voltammetry curve was rectangular; the charge and discharge test showed that at a current density of 1 A / g, its specific capacity was as high as 310 F / g. Example 2
[0028] A method for preparing a coal-based carbon tube composite hierarchical porous carbon material, comprising the following steps: The long flame coal was subjected to Soxhlet extraction with tetrahydrofuran and carbon disulfide as solvents. The ratio of coal to organic solvent was 1g:40 mL, and the extraction rate was 25%. The remaining coal sample in the extraction tube was placed in an oven at 80 ℃ and dried for 3 h to obtain the residual coal. The residual coal was mixed with KOH and K2SO4 in a mass ratio of 1:2:0.02, and after adding appropriate amount of water and stirring for 12 h, it was dried in an oven at 110 ℃ overnight and then fully ground. The mixture was loaded into a closed metal reactor and placed in a muffle furnace, heated to 950 ℃ at a heating rate of 15 ℃ / min, and kept at a constant temperature for 2 h. After the product was cooled, a crude product containing carbon nanotubes / activated carbon was obtained. The crude product was deashed at 80 ℃ for 12 h with 1.5 mol / L nitric acid and hydrofluoric acid to reduce the ash content to less than 0.5%, and then filtered, washed with water to neutrality, and dried to obtain a coal-based carbon tube composite hierarchical porous carbon material. Low temperature nitrogen adsorption-desorption analysis showed that the specific surface area of the material was 1685 m 2 / g, and the total pore volume is 0.74 cm 3 / g, and the mesoporosity is 15.6%.
[0029] The material was mixed with polyvinylidene fluoride (PVDF) at a mass ratio of 90:10, and a proper amount of N-methyl-2-pyrrolidone (NMP) was added to make a slurry and applied to a nickel foam with a diameter of 16 mm. After the solvent evaporated, it was placed in a vacuum drying oven at 100°C for 12 hours, and then a three-electrode test was performed with the nickel foam coated with active materials as the working electrode, metal platinum as the counter electrode, Hg / HgO as the reference electrode, and 6M KOH solution as the electrolyte. The electrochemical performance test showed that the material had excellent electrochemical performance for supercapacitors, and its cyclic voltammetry curve was rectangular; the charge and discharge test showed that at a current density of 1 A / g, its specific capacity was as high as 280 F / g. Example 3
[0030] A method for preparing a coal-based carbon tube composite hierarchical porous carbon material, comprising the following steps: The long flame coal was subjected to Soxhlet extraction with toluene and carbon disulfide as solvents. The ratio of coal to organic solvent was 1 g:50 mL, and the extraction rate was 28%. The remaining coal sample in the extraction tube was placed in an oven at 80 °C for 3 h to obtain the residual coal. The residual coal was mixed with NaOH and Na2SO4 in a mass ratio of 1:2:0.01, and after adding an appropriate amount of water and stirring for 12 h, it was dried in an oven at 110 °C overnight and then fully ground. The mixture was loaded into a closed metal reactor and placed in a muffle furnace. It was heated to 900 °C at a heating rate of 10 °C / min and kept at a constant temperature for 2 h. After the product was cooled, a crude product containing carbon nanotubes / activated carbon was obtained. The crude product was deashed at 80 °C for 12 h with 2 mol / L nitric acid and hydrofluoric acid to reduce the ash content to less than 0.5%, and then filtered, washed with water to neutrality, and dried to obtain a coal-based carbon tube composite hierarchical porous carbon material. Low temperature nitrogen adsorption-desorption analysis showed that the specific surface area of the material was 1388 m 2 / g, and the total pore volume is 0.66 cm 3 / g, and the mesoporosity is 22.7%.
[0031] The material was mixed with polyvinylidene fluoride (PVDF) at a mass ratio of 90:10, and a proper amount of N-methyl-2-pyrrolidone (NMP) was added to make a slurry and applied to a nickel foam with a diameter of 16 mm. After the solvent evaporated, it was placed in a vacuum drying oven at 100°C for 12 hours, and then a three-electrode test was performed with the nickel foam coated with active materials as the working electrode, metal platinum as the counter electrode, Hg / HgO as the reference electrode, and 6M KOH solution as the electrolyte. The electrochemical performance test showed that the material had excellent electrochemical performance for supercapacitors, and its cyclic voltammetry curve was rectangular; the charge and discharge test showed that at a current density of 1 A / g, its specific capacity was as high as 240 F / g. Example 4
[0032] A method for preparing a coal-based carbon tube composite hierarchical porous carbon material, comprising the following steps: Subbituminous coal was subjected to Soxhlet extraction using tetrahydrofuran and carbon disulfide as solvents. The ratio of coal to organic solvent was 1g:50 mL, and the extraction rate was 20%. The remaining coal sample in the extraction tube was placed in an oven at 80 ℃ and dried for 3 h to obtain the residual coal. The residual coal was mixed evenly with KOH and K2SO4 in a mass ratio of 1:1:0.03, and after adding an appropriate amount of water and stirring for 12 h, it was dried in an oven at 110 ℃ overnight and then fully ground. The mixture was loaded into a closed metal reactor and placed in a muffle furnace, heated to 900 ℃ at a heating rate of 5℃ / min, and kept at a constant temperature for 2 h. After the product was cooled, a crude product containing carbon nanotubes / activated carbon was obtained. The crude product was deashed at 80 ℃ for 12 h with 2 mol / L nitric acid and hydrochloric acid to reduce the ash content to less than 0.5%, and then filtered, washed with water to neutrality, and dried to obtain a coal-based carbon tube composite hierarchical porous carbon material. Low temperature nitrogen adsorption-desorption analysis showed that the specific surface area of the material was 1285 m 2 / g, and the total pore volume is 0.64 cm 3 / g, and the mesoporosity is 27.6%.
[0033] The material was mixed with polyvinylidene fluoride (PVDF) at a mass ratio of 90:10, and a proper amount of N-methyl-2-pyrrolidone (NMP) was added to make a slurry and applied to a nickel foam with a diameter of 16 mm. After the solvent evaporated, it was placed in a vacuum drying oven at 100°C for 12 hours, and then a three-electrode test was performed with the nickel foam coated with active materials as the working electrode, metal platinum as the counter electrode, Hg / HgO as the reference electrode, and 6M KOH solution as the electrolyte. The electrochemical performance test showed that the material had excellent electrochemical performance for supercapacitors, and its cyclic voltammetry curve was rectangular; the charge and discharge test showed that at a current density of 1 A / g, its specific capacity was as high as 255 F / g.
Claims
1. A method for preparing a coal-based carbon tube composite hierarchical porous carbon material, characterized in that: The following steps are involved: (1) Using the Soxhlet extraction method to remove light components from low-rank coal to obtain residual coal; (2) The raffinate coal obtained in step (1) is mixed evenly with an alkali metal catalyst and a sulfate additive, water is added and stirred, and the mixture is dried in an oven overnight, and then fully ground; (3) placing the mixture obtained in step (2) into a sealed metal reactor and heating it in a muffle furnace, and after the product is cooled, a crude product containing carbon nanotubes / activated carbon is obtained; (4) The crude product obtained in step (3) is subjected to acid washing and deashing treatment with nitric acid or hydrochloric acid at 60-80° C. to reduce the ash content to below 0.5%, and then filtered, washed with water to neutrality, and dried to obtain a coal-based carbon tube composite hierarchical porous carbon material.
2. The method for preparing a coal-based carbon tube composite hierarchical porous carbon material according to claim 1, characterized in that: The specific steps of the Soxhlet extraction method in step (1) are as follows: loading dry low-rank coal powder into a Soxhlet extraction cylinder, and injecting a low-boiling point organic solvent into the container below; after connecting the various parts of the extractor, connecting condensing water, and setting the temperature of the organic solvent constant temperature water bath to 80-140°C; extracting until the liquid in the extraction cylinder is transparent and colorless, placing the remaining coal sample in the extraction cylinder in an oven at 80°C and drying for 3 hours to obtain the residual coal, and recycling the organic solvent waste liquid by evaporation-condensation.
3. The method for preparing a coal-based carbon tube composite hierarchical porous carbon material according to claim 2, characterized in that: In step (1), the low-rank coal is one or more of lignite, long flame coal and sub-bituminous coal; the low-boiling point organic solvent is one or more of tetrahydrofuran, toluene and carbon disulfide; and the ratio of coal to organic solvent is 1 g:10-50 mL.
4. The method for preparing a coal-based carbon tube composite hierarchical porous carbon material according to claim 2, characterized in that: The extraction rate in step (1) is greater than 20%.
5. The method for preparing a coal-based carbon tube composite hierarchical porous carbon material according to claim 1, characterized in that: In step (2), the mass ratio of the extracted coal to the alkali metal catalyst and the sulfate additive is 1:1-3:0-0.
05.
6. The method for preparing a coal-based carbon tube composite hierarchical porous carbon material according to claim 1, characterized in that: The alkali metal catalyst described in step (2) is at least one of KOH, K2CO3, C6H5K3O7, NaOH and Na2CO3, and the sulfate is one of K2SO4 and Na2SO4.
7. The method for preparing a coal-based carbon tube composite hierarchical porous carbon material according to claim 1, characterized in that: In step (2), the stirring time is 6 to 12 h, and the mixture is dried in an oven at 110 °C.
8. The method for preparing a coal-based carbon tube composite hierarchical porous carbon material according to claim 1, characterized in that: In step (3), the metal reactor is made of one of high temperature and corrosion resistant 316S and 316L stainless steels, and the wall thickness is less than 5 mm. The heating conditions in the muffle furnace are: heating to 750-950°C at a heating rate of 5-15°C / min and maintaining the temperature for 1-3 h.
9. The method for preparing a coal-based carbon tube composite hierarchical porous carbon material according to claim 1, characterized in that: The concentration of nitric acid or hydrochloric acid in step (4) is 1-2 mol / L, and the deashing treatment time is 6-12 h.
10. Use of the coal-based carbon tube composite hierarchical porous carbon material obtained by the preparation method according to any one of claims 1 to 9 in the preparation of supercapacitors.
Citation Information
Patent Citations
Preparation method of supercapacitor active carbon with controllable specific surface area
CN108101054A
Activated carbon material for supercapacitor and preparation method and application thereof
CN111232975A